MODEL PEMBELAJARAN INKUIRI DAN DISCOVERY DALAM KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Imam Setiadi Putra (IKIP Siliwangi, 2022)
This study aims to determine the use of Inquiry and Discovery learning models in improving students' mathematical representation abilities. This research is a quantitative experimental research. The population in this study, namely class X at one of the high schools in Bima Regency in the 2021/2022 school year. The research sample is class X IPA 1 who gets the Inquiry learning model (experiment 1) as many as 30 students, and class X IPA 2 who gets the Discoveri learning model (experiment 2) with as many as 30 students. The data collection techniques in this study were using observation, interviews and tests, while the research instrument used a test instrument. The data analysis technique in this study used the Normality Test, Homogeneity, N-Gain Test, t-test. The research results are: 1) Inquiry and discovery learning models can improve students' mathematical representation abilities; 2) The use of the discovery learning model is better than the inquiry learning model in improving students' mathematical representation abilities.